DEVELOPING PISA-LIKE MATHEMATICS TASK WITH INDONESIA NATURAL AND CULTURAL HERITAGE AS CONTEXT TO ASSESS STUDENTS MATHEMATICAL LITERACY - Oktiningrum, Wuli; Zulkardi, Zulkardi; Hartono, Yusuf (Journal on Mathematics Education, 2016)
The aim of this research is produce a set of PISA-like mathematics task with Indonesia natural and cultural heritage as context which are valid, practical, to assess students’ mathematics literacy. This is design research using type of development research with formative evaluation. A total of 20 students of SMP Negeri 1 Palembang. Beside, 10 experts were involved in this research to assess the feasibility of prototyping in terms of content, context and language. Walk through, documentation, questionnaire, test result, and interviews are way to collect the data. This research produced a PISA-like math task is as many 12 category of content, context, and process valid, practical and has potential effect. The validity came empirical evaluation of validation and reliability testing during small group. From the field test, we conclude that the tasks also potentially effect to the students’ mathematical literacy in activating the indicators of each Fundamental Mathematical Capabilities.Keywords: development research, PISA task, mathematics literacy, fundamental mathematical capabilities DOI: http://dx.doi.org/10.22342/jme.7.1.2812.1-8